Papillary thyroid carcinoma with tracheal invasion: A case report. Issue 38 (September 2019) - Zhang, Jiateng; Fu, Chao; Cui, Kefei; Ma, Xiao
Abstract: Rationale: Compared with most malignant tumors, papillary thyroid carcinoma (PTC) is usually associated with favorable survival and low recurrence rate. The prognostic factors of PTC include age, sex, tumor size, enlarged lymph nodes, and extrathyroidal extension. Among the extrathyroidal extension, upper aerodigestive tract (ADT) invasion by PTC is a marker of more aggressive tumor behavior, defining a subpopulation of patients at a greater risk of recurrence and death. Patient concerns: A 61-year-old woman had a cervical mass that was slowly growing for three years. Additionally, she had haemoptysis of 1-year duration. During the month prior to her visit, she had difficulty breathing. Diagnosis: Neck ultrasonography (US) and thyroid computed tomography (CT) images both showed a well-defined calcified mass on the left lobe of the thyroid gland. Additionally, the thyroid CT revealed that part of the mass protruded into the lumen which resulted in the thickening on the left side of the trachea. Accordingly, her diagnoses were as follows: firstly, a solid mass on the left lobe of the thyroid gland with tracheal compression; and finally, the space-occupying airway lesion. Interventions: She underwent a bronchoscopic examination, which revealed a mass blocking most of the upper endoluminal trachea. Thus, the mass was resected at the upper tracheal segment, followed by electrotome and argon plasma coagulation treatment. She was then transferred to the Thyroid Surgery Department. Thyroid surgeons took the surgical type of bilateral subtotal thyroidectomy + exploration of bilateral recurrent laryngeal nerve + dissection of the lymph node in neck central area + circumferential sleeve resection + end-to-end anastomosis + tracheotomy in the patient. Outcomes: After surgery, she recovered well without any local recurrence or distant metastasis. Lessons: When patients with PTC have haemoptysis, hoarseness, dyspnea, or any other symptoms, and the imaging examinations reveal a space-occupying lesion in the thyroid and airway, clinicians should focus on PTC with tracheal invasion, a bronchoscopic examination must be immediately performed because the subsequent surgical management depends on the degree of tracheal invasion.